Transdermal absorption enhancement of n-terminal tat-GFP fusion protein (TG) loaded in novel low-toxic elastic anionic niosomes - Jiradej Manosroi (2018)
Elastic anionic niosomes (Tween 61/cholesterol/dicetyl phosphate at 1:1:0.05 molar ratio of 20 mM) with various concentrations of ethanol and edge activators sodium cholate (NaC) and sodium deoxycholate (NaDC) showed larger vesicular size (171.94 ± 63.52 - 683.17 ± 331.47 nm) and higher negative zeta potential (-6.45 ± 2.76 to - 17.40 ± 2.51 mV) than the nonelastic anionic niosomes. The elasticity (deformability index) and entrapment efficiency of all elastic vesicles except the NaDC vesicles were higher than the nonelastic vesicles. The morphology, under transmission electron microscope, of elastic and nonelastic niosomes loaded and not loaded with Tat-green fluorescent protein fusion protein (TG) were in large unilamellar structure. TG loaded in elastic (1 mol% NaC) anionic niosomes gave the highest cell viability both in HT-29 (92.32 ± 3.82%) and KB cells (96.62 ± 5.96%), the highest cumulative amounts (62.75 ± 2.68 μg/cm2) and fluxes (10.46 ± 3.45 μg/cm2h) in receiving chamber in rat skin transdermal study by Franz diffusion cells. This study has not only indicated the synergistic enhancement effects of the Tat peptide and the niosomal delivery system on the cellular uptake and transdermal absorption of TG but also 1 mol% NaC as an edge activator to obtain a novel low-toxic elastic anionic niosomes for topical use of therapeutic macromolecules such as proteins, as well. © 2010 Wiley-Liss, Inc. and the American Pharmacists Association.